2022
DOI: 10.1007/s12397-022-09436-z
|View full text |Cite
|
Sign up to set email alerts
|

The “Ambassadorial” Journalist: Twitter as a Performative Platform for Ultra-Orthodox Journalists during the COVID-19 Pandemic

Abstract: Journalists can play a pivotal role in promoting a population’s security amid a health crisis such as a global pandemic. This role becomes of enhanced importance for marginalized populations as they face a compounded threat due to preexisting social inequalities and exclusion. This study focuses on the utilization of Twitter by ultra-Orthodox journalists during the early months of the COVID-19 pandemic in Israel. The study applies a thematic analysis of 23,110 tweets from the 20 most popular ultra-Orthodox jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Given the piety and totality of the Haredi way of life, as discussed in literature reviews, the existence of the religious facet as a separate category came as a surprise. Specifically, when comparing our findings with previous research on Haredi journalists, communal considerations were found to trump professional ones (Golan and Mishol-Shauli 2018;Lavie et al 2023;Shomron 2022). Furthermore, it could be assumed that religion would act as an underpinning axis to guide all considerations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Given the piety and totality of the Haredi way of life, as discussed in literature reviews, the existence of the religious facet as a separate category came as a surprise. Specifically, when comparing our findings with previous research on Haredi journalists, communal considerations were found to trump professional ones (Golan and Mishol-Shauli 2018;Lavie et al 2023;Shomron 2022). Furthermore, it could be assumed that religion would act as an underpinning axis to guide all considerations.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies of Haredi journalism suggest that communal aspects carry more weight in enclaved societies (Golan and Mishol-Shauli 2018;Lavie et al 2023;Rosenberg and Blondheim 2021;Shomron 2022). Additionally, as science is regarded as knowledge that leans on ambivalent tenets of legitimacy within religious communities, its ethical considerations warrant particular examination within this conceptual framework.…”
Section: Conceptual Frameworkmentioning
confidence: 96%
“…Ultra-Orthodox people use independent sectoral media, supervised by rabbinic committees. Access to the internet as well as non-religious media and books is limited (Orr, Erblich, et al 2021; Shomron 2022; Shomron and David 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are numerous ultra-Orthodox streams, groups, and sub-groups, which differ from one another in certain aspects of religious practice and belief (Caplan and Leon 2023). The ultra-Orthodox population in Israel can roughly be divided into three main streams: Hasidic, Lithuanian, and Sephardic, each makes up around one third of the ultra-Orthodox population (Engelman et al 2020; Friedman 2021; Shomron 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rabinowitz, 2020). At the same time, others, including ultra-Orthodox journalists, contextualized the elevated morbidity levels and pointed to extenuating circumstances that are characteristic of ultra-Orthodox communities (Shomron, 2021b). These included crowded living conditions, habitual close communal activities, and a paucity of health information (e.g.…”
Section: The Covid-19 Pandemicmentioning
confidence: 99%